Nurses knowledge, attitudes and practices towards patients with HIV and AIDS in Kumasi, Ghana - Dorothy Serwaa Boakye; Azwihangwisi Helen Mavhandu-Mudzusi (Elsevier, 2019)
Background: Studies on knowledge, attitudes and practices among health care workers involved in HIV and AIDS care have often revealed the lack of knowledge about HIV and AIDS. Nurses' knowledge may compromise the quality of care and attitudes towards patients living with HIV/AIDS. Special nursing knowledge and skills have been suggested as prerequisite for taking care of patients with HIV. Purpose: The purpose of this study is to assess nurses' knowledge, attitudes and practices towards patients with HIV and AIDS in Kumasi, Ghana. Methods: A quantitative cross-sectional study was conducted among 247 nurses at five selected health facilities in the Kumasi Metropolis. Data was collected by means of structured self-administered questionnaire and analysed using SPSS version 23.0. Results were presented using charts and tables. Results: Knowledge on HIV and AIDS was satisfactory but some still hold erroneous beliefs and misconception about HIV transmission. A majority demonstrated favourable attitudes. Nurses had fears of contracting the virus, which resulted in the display of negative attitudes by some. Their practice of universal precautions was satisfactory; however there was evidence of non-compliance among some of them. Conclusion: The need for continuous in-service training of nurses on HIV and AIDS is a key contributing factor to promoting knowledge, correcting a misconception, favourable attitude and improve compliance to universal precautions and other preventive practices such as uptake of PEP. Keywords: Attitudes, HIV/AIDS, Knowledge, Nurses, Practice